PERANCANGAN RUMAH SAKIT KHUSUS MATA DENGAN PENDEKATAN ARSITEKTUR BERKELANJUTAN DI KOTA TOMOHON - Manopo, Gabriella; Lombok, Claudia Irene; Budhyowati, M. Y. Noorwahyu (Jurnal Ilmiah Desain Sains Arsitektur (DeSciArs), 2023)
The number of eye health problems in North Sulawesi, especially the city of Tomohon every year is increasing, eye damage appears at a young age to old age, the city of Tomohon is also the city with the highest number of eye damage but at this time eye health facilities or public hospitals have not fully guaranteed the health and comfort and even facilities for eye patients so that eye patients must go far from the city of Tomohon to get this special eye health facility Because Tomohon City does not have a special eye hospital while it is not comparable to the number of eye damage that has increased in Tomohon City, it is an alternative that Tomohon City needs a special eye hospital. The goal is to provide health facilities or hospitals to reduce the number of eye damage in the city of Tomohon that is comfortable and able to improve special health facilities in the city of Tomohon. This design begins with data collection, followed by site analysis, the design concept used in this design is sustainable architecture in accordance with the goals of Tomohon city for long-term development by building sustainable buildings. The result of this design is a special eye hospital that is sustainable and meets specialized health facilities. The concept of sustainable architecture to be implemented is an energy-efficient building.